Bumpy Application of Utility Code for Genomic Inventions: With Special Reference to Express Sequence Tags - Murthy, M R Sreenivasa; Syamala, K; Yadav, Harshavardhan (International Journal of Applied Sciences and Biotechnology, 2013)
Genomics, a new bough of biotechnology responsible for gene mapping has acquired a rapid significance in the field of patents. Brisk growth of patent filing in genomic subject matter is raising serious concerns about their utility from the perspective of societal benefit. Though the genomic related patent application qualifies the criterion of invention and non-obviousness in major instances, the inventors are unable to satisfy the utility criterion. Some instances such as patent application for ESTs have no utility at all. The patent regulators constructed various tests to deal with the situation such as specificity, substantiality (real world) credibility tests etc. Hoverer, it is noteworthy that an attempt to uniform the standard of utility test for genomic inventions especially in the field of ESTs, cloning and creation of chimeras, has been made by America and Europe through specific regulations. Thus, the objective of this paper is firstly, to explain the importance of biotechnology and genomic inventions for mankind and significance of ESTs for future research. Secondly, to analyze the application of Utility code prior to the emergence of Utility code in America and Europe. Thirdly to scrutinize the Utility code in both countries and their implication on aftermath cases, and. fourthly and finally, to critically evaluate the both countries utility pathways in the light of societal benefit. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.8959 Int J Appl Sci Biotechnol, Vol. 1(4): 189-196